2014
DOI: 10.1038/cdd.2014.145
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and NF-κB co-activation triggered by TLR3 stimulation facilitates stem cell-like phenotypes in breast cancer

Abstract: Cancer stem cells (CSCs) are responsible for tumor initiation and progression. Toll-like receptors (TLRs) are highly expressed in cancer cells and associated with poor prognosis. However, a linkage between CSCs and TLRs is unclear, and potential intervention strategies to prevent TLR stimulation-induced CSC formation and underlying mechanisms are lacking. Here, we demonstrate that stimulation of toll-like receptor 3 (TLR3) promotes breast cancer cells toward a CSC phenotype in vitro and in vivo. Importantly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 42 publications
3
80
0
Order By: Relevance
“…17.3a, b ). Our result which corresponds with recent study indicated that activation of TLR3 by poly(I:C) promoted the cancer stem cell phenotype by upregulating the pluripotent genes including SOX2 in breast cancer [ 18 ]. Moreover, the increased mRNA level of hair progenitor-specifi c marker has been observed upon TLR3 activation in keratinocyte which contributed to hair follicle regeneration [ 17 ].…”
Section: Tlr3 Activation Promote Stemness Of Pdlscssupporting
confidence: 91%
“…17.3a, b ). Our result which corresponds with recent study indicated that activation of TLR3 by poly(I:C) promoted the cancer stem cell phenotype by upregulating the pluripotent genes including SOX2 in breast cancer [ 18 ]. Moreover, the increased mRNA level of hair progenitor-specifi c marker has been observed upon TLR3 activation in keratinocyte which contributed to hair follicle regeneration [ 17 ].…”
Section: Tlr3 Activation Promote Stemness Of Pdlscssupporting
confidence: 91%
“…39 Positive TLR3 expression was considered a favorable prognostic factor whereas positive c-Myc protein expression is a poor prognostic factor by clinical research of NB. 8,20 However, elevated TLR3 expression in breast cancer and overexpression of c-Myc in HER2-positive breast cancer were respectively determined as a poor prognostic factor, 40,41 and TLR3 treatment was associated with overexpression of c-Myc to facilitate stem cells potential. 40 In addition, overexpression of TLR3 and c-Myc was reported to be induced by poly(I:C) treatment, which led to cell proliferation in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 However, elevated TLR3 expression in breast cancer and overexpression of c-Myc in HER2-positive breast cancer were respectively determined as a poor prognostic factor, 40,41 and TLR3 treatment was associated with overexpression of c-Myc to facilitate stem cells potential. 40 In addition, overexpression of TLR3 and c-Myc was reported to be induced by poly(I:C) treatment, which led to cell proliferation in head and neck cancer. 42 These reports indicate that the roles of TLR3 and c-Myc in innate immune system and their responses to poly(I:C) treatment might be type-specific for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…70 In line with these data, experiments in breast cancer cells put in evidence that NF-kB and b-catenin signaling downstream of TLR3 promoted the enrichment of a subset of cells with CSC phenotype. 71 Similarly, in the haematopoietic stem/progenitor cell (HSPC) compartment, chronic Type-I-IFN stimulation resulted in HSPC loss of quiescence and dysfunction. 72 This phenomenon was mainly due to Type-I-IFN-induced accumulation of reactive oxygen species (ROS).…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 99%